Pengaruh Gaya Kepemimpinan Dan Beban Kerja Terhadap Kinerja Pegawai Pada Badan Perencanaan Penelitian Dan Pengembangan (BAPPEPAN) Kabupaten Mamuju - Muhtar, Muhtar (LPPM Universitas Muhammadiyah Mamuju, 2022)
The research was conducted at the Research and Development Planning Agency (BAPPEPAN) office by observing two independent variables, namely leadership style and workload on one variable, namely employee performance. This study uses multiple linear regression using 75 samples. The results of the analysis for the leadership style variable (X1), obtained the value of Sig = 0.001, using a significant limit of a = 0.05 it can be seen that the value of Sig = 0.001 <a = 0.05 and tcount = 3,497 > ttable = 1,993. The results of the analysis for the workload variable (X2), obtained the value of Sig = 0.009, using a significant limit of a = 0.05 it can be seen that the value of Sig = 0.009 < a ​​= 0.05 and tcount = 3,263 > ttable = 1,993. This means that workload has a significant influence on employee performance at the Office of the Research and Development Planning Agency (BAPPEPAN) of Mamuju Regency